P02 Efficacy of intravenous metoprolol for heart rate control in patients undergoing CT coronary angiography. (7th September 2020) - Hoe, Mei-Lian; Qayyum, Shahzad; Auger, Dominique; Damani, Nizar; Griguer, Anne; Jain, Piyush; Keenan, Niall; Khan, Masood; Prabhakar, Anisha; Rosenfeld, Kevin; Sehmi, Joban
Abstract : Introduction: Computer tomography coronary angiography (CTCA) can be performed with improved image quality and at lower radiation dose when heart rate is lowered to less than 60 beats per minute (bpm). In our centre intravenous Metoprolol is administered on the CT table targeting a heart rate below 60 bpm. The aim of this audit was to assess the efficacy of intravenous beta-blockade to achieve optimal heart rates in patients undergoing CTCA. Methods: We carried out a retrospective case note review of all patients undergoing CTCA between 1 – 30 November 2018. Scanning was performed using a 320-detector row scanner with prospective gating (Toshiba Aquilon One). Data collected included attending radiologist/cardiologist, dose of Metoprolol, heart rate at time of image acquisition and baseline patient characteristics. Results: Case notes of 131 consecutive patients referred for CTCA were reviewed. The mean heart rate achieved was 61.7 bpm (range 30–130 bpm). The average administered dose of metoprolol was 15.5 mg (range 0–60 mg). 51% of patients achieved a heart rate less than 60 bpm at the time of scanning. For patients achieving target heart rates below 60 bpm the average dose of metoprolol was 9.3 mg, and 22.4 mg for those with heart rates greater than 60 bpm at the time of image acquisition. Conclusion: Routine administration of intravenous beta-blocker peri-procedure fails to achieve optimal heart rate control in approximately half of all patients undergoing CTCA. Alternative protocols including pre-treatment with a short course of oral beta-blockers should be considered.